PENGENALAN KONSEP PERKALIAN PADA ANAK USIA DINI MENGGUNAKAN MEDIA BAHAN ALAM: INTRODUCTION TO THE CONCEPT OF MULTIPLICATION IN EARLY CHILDREN USING NATURAL MATERIALS - Lathipah Hasanah; Nadine Bong; Naila Fakhira; Alya Shafira; Catur Wulandari (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2022)
Mathematics is the science of numbers, the relationship between numbers, and the operational procedures used in solving problems concerning numbers. Mathematics comes from the Latin word mathematica, which was originally taken from the Greek word mathematic, which means